Terrorism risk forecasting by ideology - Onat, Ismail (European journal on criminal policy and research, 2019)
The purpose of the present study is to produce foresights on terrorism. For the first time in the literature, we test the predictive validity of risk terrain modeling to forecast terrorism. Because the relevant literature suggests that target selection and the places where terrorist attacks occur are related to a group’s strategies, we also investigate whether and how violent terrorist acts vary with respect to their surroundings in the same jurisdiction when the ideology is the point of comparison. Separatist and leftist terrorist groups committed 1152 violent terrorist acts between 2008 and 2012 in Istanbul, Turkey. Our analysis begins with a comparison of targets and risk factors by the ideology of the perpetrators for 857 separatist and 295 leftist terrorist incidents. After identifying high-risk locations, we test the predictive validity of risk terrain modeling. The study results showed that context and spatial influence—the risky areas of terrorism—vary by the nature of the ideology in the jurisdiction. Practical implications also are discussed.